BEHAVIORAL PROBLEMS RELATED WITH INTERNET USAGE: AN EXPLORATORY STUDY - De Gracia Blanco, Manuel; Vigo Anglada, Marc; Fernández Pérez, Mª José; Marcó Arbonès, María (Anales de Psicología / Annals of Psychology, 2002)
The pathological usage of Internet has been described in the psychological literature as "Addiction to Internet" or as "Pathological Usage of Internet". This study tries to identify the possible effects related with Internet usage. A web survey was designed and broadcasted through Internet during 4 weeks. The sample was formed by 1664 volunteer respondents of either sex. The cluster analysis of the answers has identified a subset of users (4.9% of the sample) who declared having frequent problems with Internet usage, such as feeling of being guilty, craving of being connected, loose of control, or time wasting. This group showed a higher anxiety and social disfunction, evaluated through the GHQ-28, than the rest of the sample. They also access more frequently to chat services and adult pages. We conclude that the survey being used identifies in an homogeneous way the problems related with Internet usage (=0.91), and an acceptable concurrent validity with the criterion items used (r=0.60). Finally, methodological limitations of web - designed study surveys are discussed.